Ezer in the Context of Men Creation in Genesis 2:4b-25 - Simbolon, Lena Christina (the International Journal of Education, Theology, and Humanities, 2023)
In the story of human creation written in the book of Genesis 2:4b-25, it is stated that the Lord God saw that it was not good for humans to be alone, so God made a suitable helper (ezer) for Adam. He created the woman from Adam's rib. Women were created by God as helpers equal to men. This states that women are not inferior to men, but to state that women are men's partners in carrying out the tasks and responsibilities that God has given to humans.